Marked disruption and aberrant regulation of elastic fibres in early striae gravidarum. (8th November 2015) - Wang, F.; Calderone, K.; Smith, N.R.; Do, T.T.; Helfrich, Y.R.; Johnson, T.R.B.; Kang, S.; Voorhees, J.J.; Fisher, G.J.
Summary: Background: Striae gravidarum (SG), or 'stretch marks' of pregnancy, begin as erythematous streaks, and mature over months to years to become permanent scar‐like bands that may be hypopigmented, atrophic and lax. Objectives: To investigate early molecular alterations that may promote laxity of mature SG, we investigated the dermal elastic fibre network, which provides human skin with elastic properties. Methods: We obtained skin samples of newly developed, erythematous abdominal SG in healthy pregnant women. The elastic fibre network was examined by Verhoeff elastic staining and immunofluorescence staining of skin sections. Gene expression was measured by real‐time polymerase chain reaction. Results: The normal elastic fibre network appeared markedly disrupted in SG, compared with perilesional abdominal skin or control (normal‐appearing hip skin). This disruption was accompanied by the emergence of short, disorganized, thin, thread‐like 'fibrils', which were observed prominently in the mid‐to‐deep dermis. These fibrils were rich in tropoelastin (the main component of normal elastic fibres), and persisted into the postpartum period without forming normal‐appearing elastic fibres. The emergence of these fibrils was accompanied by increased gene expression of tropoelastin and fibrillin‐1, but not other elastic fibre components, including fibrillin‐2 and fibulin‐1, ‐2 or ‐5. Conclusions: In early SG, the elastic fibre network appears markedly disrupted, and newly synthesized tropoelastin‐rich fibrils emerge, likely as a result of uncoordinated synthesis of elastic fibre components. Because they are thin and disorganized, tropoelastin‐rich fibrils likely do not function as normal elastic fibres do. These observations provide the foundations for elucidating pathogenic mechanisms by which laxity may develop in SG. Abstract : What's already known about this topic? Surprisingly little is known about the dermal alterations affecting striae gravidarum (SG), or stretch marks of pregnancy. Dermal elastic fibres, which are composed mainly of tropoelastin, provide human skin with elastic properties. What does this study add? We extensively analysed elastic fibres in early SG, and observed marked disruption of the normal elastic network, accompanied by the emergence of newly synthesized, disorganized, persistent, thin tropoelastin‐rich fibrils. These alterations may promote laxity of mature SG lesions. Linked Comment: Watson, Br J Dermatol 2015; 173: 1359–60 .